Analysis Of Madrasah Teacher Competencies: The Main Pillar Of Improving The Quality Of Islamic Education Learning - Siti Hamidatul Aslamiyah; Athirohtul Salwa; Dhiki Amrulloh; Hinggil Permana (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The purpose of this study is to analyze teacher teaching competency in improving the quality of learning at Madrasah Ibtidaiyah (MI) Nurul Huda. The study aims to evaluate aspects of teacher competency, including pedagogical knowledge, communication skills, and the application of innovative learning methods. This research approach is qualitative with a case study design. Data collection through interviews, observations, and document analysis. Data validation with triangulation and data analysis using data reduction, data presentation, and conclusion drawing. The results of the study indicate that teacher competency at MI Nurul Huda has a significant influence on the quality of learning received by students. Factors that influence teacher competency include professional training, teaching experience, and support from the school. In addition, this study also discusses relevant learning theories, such as Constructivism Theory, which emphasizes the importance of the active role of students in the learning process. The findings of this study are expected to provide recommendations for MI Nurul Huda managers and policymakers in designing sustainable teacher competency development programs. Thus, it is hoped that the quality of education at the institution can improve, so that students can reach their maximum potential in the learning process. This research makes an important contribution to the development of education at the elementary level, especially in the madrasah context.